Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Cover crop-specific root-derived biopore structure is associated with biopore sheath bacterial facets in compacted soil columns - Peng Xiong; Guilong Li; Zejun Luo; Hao Li; Zhengfu Yue; Yueming Chen; Xiaolin He; Xiong Fang; Jia Liu; Jingjing Peng (Soil and Tillage Research, 2026)

Spatial confinement in zeolites dominates pentene monomolecular cracking pathway - Fang Li; Weiyong Zhong; Min Sun; Yiran Wang; Penghe Zhang; Yueming Liu; Mingyuan He (Chemical Engineering Journal, 2026)

Alpha-ketoglutaric acid alleviates litchi fruit browning and senescence via enhancing antioxidant capacity and energy homeostasis - Yuemin Yang; Rufang Deng; Mengting Liu; Xinguo Su; Yueming Jiang; Xuewu Duan; Guoxiang Jiang; Ting Li (Postharvest Biology and Technology, 2026)

Mg/Fe-layered double hydroxide-loaded biochar enhances nitrogen retention and reduces geochemically reactive metal concentrations in paddy soil: Bacterial community responses - Hengxin Liu; Ruohan Li; Yueming Han; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

FreqChange: Frequency-aware spatiotemporal learning with prior guidance for semantic change detection in remote sensing images - Haiyan Huang; Zhenfeng Shao; Duowang Zhu; Xiao Huang; Ruiqian Zhang; Qimin Cheng; Jindou Zhang; Yueming Duan; Deren Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Musa acuminata calmodulin-binding transcription activator 4 enhances fruit quality maintenance of banana during cold storage - Ying Li; Youxia Shan; Wanqi Chen; Rufang Deng; Xuewu Duan; Taotao Li; Yueming Jiang (Food Chemistry, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Arachidonic acid enhances chilling tolerance in banana fruit via coordinated antioxidant system, energy homeostasis and phenylpropanoid metabolism - Youxia Shan; Ying Li; Taotao Li; Wanqi Chen; Xuewu Duan; Yueming Jiang (Food Chemistry, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Epigenetic activation of lignin biosynthesis by CsJMJ16 confers enhanced resistance to Penicillium digitatum in citrus - Jing Zeng; Ting Li; Mengting Liu; Xiaoyan Duan; Jiechun Peng; Zhiwei Li; Guoxiang Jiang; Yueming Jiang; Xuewu Duan (Postharvest Biology and Technology, 2026)

A hybrid MIMO-CNN-BiLSTM-AM model for efficient prediction of motion responses and mooring tension of FOWTs - Xiaojie Tian; Xiaolong Wang; Zhi Li; Yueming Zheng; Wei Deng (Ocean Engineering, 2026)

Sealing behavior of bolted flange system with double metallic C-rings during prolonged high-temperature operation - Yijun Chai; Yunzhou Wu; Wenhao Yu; Qin Ma; Xiongwei Yang; Yueming Li (Annals of Nuclear Energy, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Organic matter supply triggers rapid microbial-driven changes in carbon-nitrogen cycling in subterranean estuary sediments - Danqing Sun; Longyun Lai; Yueming Wu; Ying Wu; Jian Li; J. Severino P. Ibánhez; Shan Jiang (Marine Chemistry, 2026)

Exploring relaxation features for rapid identification of olive oil adulteration via low-field nuclear magnetic resonance integrated with chemometrics - Yulong Chen; Xuewen Qin; Shan Zeng; Bing Li; Yueming Tao; Huanjun Hu (Food Research International, 2026)

Temporal-spatial characteristics of surface cracks during landslide evolution - Pengju An; Qinglu Deng; Yueming Yin; Weibo Li; Kai He; Kun Fang (Engineering Geology, 2026)

An on-tissue parallel d0/d20-meladrazine derivatization approach for fatty acid peroxidation products imaging in adult zebrafish - Ji Yang; Yue Sun; Yueming Li; Zhonghua Wang; Zeper Abliz; Zhi Zhou (Analytica Chimica Acta, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Distinct mowing effects on organic carbon storage and dynamics in Spartina alterniflora and Phragmites australis sediments - Yueming Wu; Danqing Sun; Shan Jiang; Beiyun Xu; Jing Liu; Jian Li; Yiyun Wang; Ying Wu (Ocean & Coastal Management, 2026)

Adenine regulates chilling injury via energy signaling salvage by purine permease MaPUP4 in banana fruit - Youxia Shan; Ying Li; Wanqi Chen; Junxian He; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Physicochemical properties of edible oxidized gum arabic–polylysine crosslinked films and their effects on the postharvest preservation of litchi - Dan Li; Huirong Cheng; Ling Xie; Hong Luo; Dandan Zhang; Jupeng Zhao; Yueming Jiang; Liang Gong (Postharvest Biology and Technology, 2026)

Total replacement of soy with alternative plant-based ingredients, feed enzymes and a probiotic in a mixed-cereal broiler diet fed during an entire growth cycle - Yueming Dersjant-Li; Abiodun Bello; Leon Marchal; Qiong Wang; Kirsty Gibbs; Jos.G.M. Houdijk (Animal Feed Science and Technology, 2026)

Does algal trophic mode affect the removal of norfloxacin? Insights from Tetradesmus obliquus - Musheng Ji; Jin Qian; Xiaxia Li; Yueming Zhu; Yin Liu; Bianhe Lu; Sijing Tang; Junwei Shen; Yuhang Zong (Journal of Hazardous Materials, 2026)

Application of riboflavin delays the browning of harvested litchi during storage at room temperature - Jiechun Peng; Ting Li; Mengting Liu; Jiangtao Zhang; Xiaoyan Duan; Ying Li; Hanzhi Liang; Pedro Garcia-Caparros; Yueming Jiang; Xuewu Duan (Food Control, 2026)

Drivers of soil carbon and nitrogen cycling during plantation succession: linking aboveground plant communities with belowground microbial networks - Xianghua Zuo; Wei Zhao; Jinying Li; Yunxiao He; Yueming Zhao; Ming Xing; Jiangnan Li; Xia Chen (Plant and Soil, 2026)

Bromide-containing surfactants enabling singlet oxygen-dominated non-radical oxidation process for efficient degradation of aromatic pollutants in soil and groundwater - Yueming Han; Zhuolun Li; Guanqing Chen; Hengxin Liu; Shichao Feng; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Apyrase MaAPY2 regulates the chilling tolerance of banana fruit as a negative modulator - Ying Li; Wanqi Chen; Shule Chen; Zhuojia Mao; Shihan Huang; Rufang Deng; Dandan Zhang; Taotao Li; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Arachidin-2 suppresses Peronophythora litchii and postharvest decay of litchi fruit - Bailin Li; Xueying Meng; Fen Liu; Bao Yang; Sui Kiat Chang; Yueming Jiang (Food Chemistry, 2026)

Dihydromyricetin inhibited DNA methyltransferases activity in citrus fruit to enhance resistance against Penicillium italicum infection - Yanling Ren; Xin Xu; Ying Li; Jianbo Xiao; Yueming Jiang; Taotao Li (Postharvest Biology and Technology, 2025)

Corrigendum to “Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit” [Postharvest Biol. Technol. 224 (2025) 113466] - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Montmorillonite-derived Mg-doped NaAlSiO4 for radiative cooling applications - Zhizheng Xiang; Zhongqiu Tong; Haowei Yang; Jie Yu; Yingjun Xiao; Yueming Wang; Shaoyuan Li; Xingang Li; Mikhail M. Mikhailov; Wenhui Ma (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Physiological and Metabolomic Analysis in Roots of Hordeum jubatum L. In Response to Iso-osmotic Stress - Peilin Han; Xiaolin Di; Bing Gao; Jinji Han; Yueming Li; Xiaoxia Deng; Zhuoran Tan; Jingnan Zhang; Jinghong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Alveolar macrophages polarization switch via α2-adrenoceptor activation ameliorates pulmonary inflammation following kidney ischemia reperfusion - Jieyu Li; Zhigang Qin; Xinhai He; Ling Jiang; Xiangfeng Liu; Zhengwei Xue; Xiao Li; Yueming Xu; Peng Li; Jianteng Gu (Inflammation Research, 2025)

New insights of licorice (Glycyrrhiza genus) as a functional food - Lulu Shao; Bailin Li; Yueming Jiang; Bao Yang (Food Chemistry, 2025)

Porphyrin-heptazine framework photosensitizers for hypoxia-tolerant pyroptotic photo-immunotherapy via enhanced radical production - Debabrata Dutta; Yueming Xue; Qinghao Zhou; Yuanyuan Ji; Shikuo Li; Zhishen Ge (Chemical Engineering Journal, 2025)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

The interfacial optimization and p-n heterojunction construction in nanozyme for improved laccase-mimic and antibiofouling activities - Xueying Qi; Junjun Lu; Yueming Li; Xinxin Xu (Journal of Environmental Chemical Engineering, 2025)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Water Body Characterization and Classification in Coal Mining Subsidence Areas: Insights from the Huainan Coalfield - Yueming Sun; Yanling Zhao; Zhibin Li; Yanjie Tang (Natural Resources Research, 2025)

Phase congruency image mosaicking approach for aerial mid-wave infrared low-overlap array scanning images - Jiani He; Yueming Wang; Lixia Deng; Yitao Li; Zhao-Liang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

In vivo cell migratory behavior drives therapeutic efficacy evidenced by SWIR fluorescence imaging - Huizhu Li; Xiao Zhang; Shunyao Li; Yueming Wang; Shingo Ogura; Kemeng Shao; Xiner Du; Yan Wo; Shiyi Chen; Jun Chen; Xuanfeng Qin; Yunxia Li; et al. (Chemical Engineering Journal, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Passive Synthetic Aperture for Direction-of-Arrival Estimation Using an Underwater Glider with a Single Hydrophone - Yueming Ma; Jie Sun; Shuo Li; Tianze Hu; Shilong Li; Yuexing Zhang (Journal of Marine Science and Engineering, 2025)
This paper addresses the aperture limitation problem faced by array-equipped underwater gliders (UGs) in direction-of-arrival (DOA) estimation. A passive synthetic aperture (PSA) method for DOA estimation using a single hydrophone mounted on a UG is proposed. This method uses the motion of the UG to synthesize a linear array whose elements are positioned to acquire the target signal, thereby increasing the array aperture. The dead-reckoning method is used to determine the underwater trajectory of the UG, and the UG’s trajectory was corrected by the UG motion parameters, from which the array shape was adjusted accordingly and the position of the array elements was corrected. Additionally, array distortion caused by movement offsets due to ocean currents underwent linearization, reducing computational complexity. To validate the proposed method, a sea trial was conducted in the South China Sea using the Haiyi 1000 UG equipped with a hydrophone, and its effectiveness was demonstrated through the processing of the collected data. The performance of DOA estimation prior to and following UG trajectory correction was compared to evaluate the impact of ocean currents on target DOA estimation accuracy.

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Epigenetic regulation on fungal disease affecting plant-based food: A review from the perspectives of host, pathogen and their interactions - Yanling Ren; Linyan Feng; Xin Xu; Jianbo Xiao; Yueming Jiang; Taotao Li (Food Bioscience, 2025)

MAPK signaling mediated intestinal inflammation induced by endoplasmic reticulum stress and NOD2 - Siyuan Peng; Yan Zhao; Wang Jiang; Yan Long; Tian Hu; Mengling Li; Jinyue Hu; Yueming Shen (Molecular and Cellular Biochemistry, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Conditional generative adversarial network (cGAN) for generating building load profiles with photovoltaics and electric vehicles - Yuewei Li; Bing Dong; Yueming Qiu (Energy and Buildings, 2025)

Transient Power Stabilization in Marine Microgrids: Improved Droop Control and Feedforward Strategies for Heterogeneous Gas Turbines with Hybrid Energy Storage - Zemin Ding; Yueming Li; Yongbao Liu; Youhong Yu (Journal of Marine Science and Engineering, 2025)
To address the complexity of power allocation in parallel operation systems combining single-shaft and split-shaft gas turbine generators, this paper proposes a coordinated power allocation strategy based on enhanced voltage droop control for marine power systems integrated with hybrid energy storage comprising flywheel and battery subsystems. Furthermore, to mitigate significant power sharing deviations during transient/pulsed load conditions in shipboard application, a feedforward compensation strategy is developed. Simulation results demonstrate that the improved droop control maintains power sharing deviations below 3.5% across steady-state operations and gradual load variations, ensuring system stability and balanced power distribution. However, abrupt load changes induce over 20% deviations, compromising parallel operation reliability. The proposed feedforward compensation strategy effectively restricts deviations within 4% under specified transient and pulsed load scenarios, satisfying both parallel operation criteria and grid power quality requirements. Validation is performed on a parallel system comprising two distinct gas turbine configurations.

Corrigendum to ''Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis'' [Postharvest Biol. Technol., vol., 222, April 2025, 113338] - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Transcription factor AcAGL9 and AcBEH1 synergistically regulate carotenoid biosynthesis during pineapple fruit ripening - Mengting Liu; Ting Li; Rufang Deng; Zhengke Zhang; Yijie Zhou; Xuewu Duan; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Evaluation of factors influencing full wave equation depth migration - Anyu Li; Yueming Ye; Xiangyu Zhu; Tao Liu; Huimin Zhang; Yong Xia (Journal of Applied Geophysics, 2025)

Effects of storage durations on flavour and bacterial communities in Liupao tea - Yueming Liang; Zhusheng Liu; Yuelan Pang; Min Li; Shengmeng Zheng; Fujing Pan; Chunyu Guo; Qianhua Wu; Ting Chen; Qiang Li; Zhonghua Liu (Food Chemistry, 2025)

Purification and identification of antioxidant activity and angiotensin converting enzyme (ACE) inhibitory activity peptide of peanut protein based on ultrafiltration (UF) membrane separation - Bin Cao; Qi Li; Zhenyu Chen; Xiuren Tang; Hock Eng Khoo; Tiemin Jiang; Yueming Jiang; Jing Li; Xinhong Dong (Food Bioscience, 2025)

Spatial extraction of sea-cucumber aquaculture ponds using remote sensing spectral and temporal features - Ruoqi Du; He Li; Chong Huang; Qingsheng Liu; Yueming Liu; Zhihua Wang (Frontiers in Marine Science, 2025)
The spatial distribution of aquaculture ponds plays a critical role in the layout, management, and evaluation of the aquaculture industry. While extensive research has been conducted on aquaculture pond extraction and monitoring, studies focusing on the differentiation of aquaculture ponds by species remain limited. The similar shapes and spectral features of water bodies associated with different species pose a challenge for extraction. A method for extracting sea-cucumber aquaculture ponds is proposed based on spectral temporal features using Sentinel-2 satellite imagery in this study. The method involves selecting the optimal sensitive spectral bands or combinations to construct two remote sensing indices of land-based aquaculture ponds. Using a time-series dataset of these indices, three key features—the mean and two slopes—are extracted. The corresponding time windows and thresholds for these key features are identified to develop a decision-tree algorithm for extracting sea-cucumber ponds. This method was applied to coastal aquaculture zones in Liaoning Province, China, to identify the spatial distribution of sea-cucumber aquaculture ponds in 2016 and 2023. The results showed that: (1) the proposed method achieved high extraction accuracy, with an overall accuracy of 79.24%; (2) Total area of sea-cucumber ponds in Liaoning Province was 931.08 km 2 , primarily located along the Huludao Xingcheng-Jinzhou Linghai and Yingkou Xishi-Dalian Zhuanghe coastal zones; (3) Over the past seven years, the area of sea-cucumber ponds increased by 624.57 km 2 , with expansion concentrated on the northwest coast of Liaodong Bay and both the eastern and western sides of the Liaodong Peninsula. These findings provide scientific support for the sustainable development of sea-cucumber aquaculture.

The effect of resveratrol on lead-induced oxidative damage and apoptosis in HT-22 cells - Xiang Yi; Ruokun Wei; Shaoni Huang; Peiqi Wei; HuiShuai Li; Zhenning Li; Michael Aschner; Yueming Jiang; Shiyan Ou; Shaojun Li (Food and Chemical Toxicology, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Arabinogalacturonan in functional food “Astragalus membranaceus root”: Structure and immunomodulatory activity - Zhili Sheng; Hui Liu; Bailin Li; Hong Zhu; Yueming Jiang; Bao Yang (Food Hydrocolloids, 2025)

Higher dynamic and turnover yet enhanced organic carbon burial in Spartina alterniflora sediments: A case study in a temperate coastal wetland - Yueming Wu; Beiyun Xu; Danqing Sun; Shan Jiang; Jian Li; Yiyun Wang; Ying Wu (CATENA, 2025)

Progress in Preparation Technology and Functional Research On Marine Bioactive Peptides - Jing Wang; Fengcheng Li; Wenjun Li; Yueming Li; Jian Zhang; Song Qin (Marine Biotechnology, 2025)

Phytosulfokine treatment delays browning of litchi pericarps during storage at room temperature - Hanzhi Liang; Yanxuan Zhu; Zhiwei Li; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

Identification of novel natural anti-browning agents based on phenotypic and metabolites differences in potato cultivars - Yueming Tang; Yiwen Yang; Fangyao Luo; Jinghong Luo; Jianjun Hu; Haoqiang Yu; Wanchen Li; Jia Gao; Fengling Fu (Food Chemistry, 2025)

Multifunctional neuroimmunoregulatory nanoenzyme-enhanced hydrogel promotes bone regeneration by improving bone healing microenvironment - Qiujiang Li; Xingxia Long; Linnan Wang; Xi Yang; Huiliang Yang; Bowen Hu; Ce Zhu; Zhuang Zhang; Zhipeng Deng; Junhu Li; Shuxin Zheng; Lei Wang; et al. (Chemical Engineering Journal, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

Functional analysis of LcDORN1 genes in the senescence of litchi fruit - Yijie Zhou; Zhiwei Li; Xiangjin Kong; Jiaqi Xiao; Yueming Jiang; Xinguo Su; Hongxia Qu (Postharvest Biology and Technology, 2024)

Continuous-flow degradation of Orange I using CoFe2O4-loaded activated carbon catalyst: Optimization of reaction parameters and toxicity prediction - Meiqi Li; Yuan Zong; Jing Feng; Hexin Zhang; Chengying Bai; Yueming Ren (Chemical Engineering Journal, 2024)

A Tank Experiment of the Autonomous Detection of Seabed-Contacting Segments for Submarine Pipelaying Operations - Bo Wang; Jie Wang; Chen Zheng; Ye Li; Jian Cao; Yueming Li (Journal of Marine Science and Engineering, 2024)
Due to the weak structural features of pipelines and underwater light attenuation, the complex and harsh environment of the seabed greatly increases the possibility of an underwater autonomous remotely operated vehicle losing a detected seabed-contacting segment during pipe-laying operations. To address this problem, we propose a cascade attention module and a prefusion module with a convolutional neural network. The cascade attention module samples the feature maps in a non-convolutional form to realize the interaction between structure and channels, and the attention map is generated by cascading attention. The prefusion module pre-fuses the three layers of feature maps from different stages in the backbone, and the delicate features of the shallow feature maps are fused with the deeper feature maps to generate richer feature maps with space location and semantic classification information. We conduct experiments to verify our modules, both on the underwater pipeline dataset and in a tank test. The results show that our modules can improve the performance of different neural network models for seabed-contacting segment detection. The target detection and instance segmentation performance of the best model is improved through a 6.3% increase in AP and a 3.8% increase in mean intersection over union compared with the baseline model.

Vitexin is a potential postharvest treatment for ameliorating litchi fruit pericarp browning by regulating autophagy - Qiuxiao Yang; Dingding Shi; Yanling Ren; Chao Yang; Hongxia Qu; Yueming Jiang; Taotao Li (Postharvest Biology and Technology, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

Acid strength controlled reaction pathways of propylene conversion under olefin cracking conditions over ZSM-5 - Qin Zhao; Fang Li; Yiran Wang; Yueming Liu; Mingyuan He (Fuel, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Sodium selenite enhances the production of functional proteins and biomass in Chlorella pyrenoidosa 038F by promoting acetate assimilation under heterotrophic cultivation - Jingjing Shangguan; Na Yang; Litao Zhang; Jianguo Liu; Yueming Li; Jianchun Xu; Xiuluan Xia; Bingzheng Xu (Aquaculture, 2024)

Hydrogen peroxide receptors regulate chilling injury of banana fruit during low-temperature storage - Shuting Zhang; Youxia Shan; Ying Li; Junxian He; Yueming Jiang (Postharvest Biology and Technology, 2024)

Insight into the aroma and taste enrichment pattern in Chinese traditional braised soup based on HS-SPME-GC-MS and HS-GC-IMS - Feifei Wang; Debin Guo; Pingwei Wen; Haiqi Chen; Yueming Hu; Jun Li; Zongcai Tu; Hui Wang (Food Bioscience, 2024)

Lead exposure induces neurodysfunction through caspase-1-mediated neuronal pyroptosis - Dongjie Peng; Leilei Wang; Yuanyuan Fang; Lili Lu; Zhaocong Li; Siyang Jiang; Jing Chen; Michael Aschner; Shaojun Li; Yueming Jiang (Environmental Research, 2024)

A Method for Multi-AUV Cooperative Area Search in Unknown Environment Based on Reinforcement Learning - Yueming Li; Mingquan Ma; Jian Cao; Guobin Luo; Depeng Wang; Weiqiang Chen (Journal of Marine Science and Engineering, 2024)
As an emerging direction of multi-agent collaborative control technology, multiple autonomous underwater vehicle (multi-AUV) cooperative area search technology has played an important role in civilian fields such as marine resource exploration and development, marine rescue, and marine scientific expeditions, as well as in military fields such as mine countermeasures and military underwater reconnaissance. At present, as we continue to explore the ocean, the environment in which AUVs perform search tasks is mostly unknown, with many uncertainties such as obstacles, which places high demands on the autonomous decision-making capabilities of AUVs. Moreover, considering the limited detection capability of a single AUV in underwater environments, while the area searched by the AUV is constantly expanding, a single AUV cannot obtain global state information in real time and can only make behavioral decisions based on local observation information, which adversely affects the coordination between AUVs and the search efficiency of multi-AUV systems. Therefore, in order to face increasingly challenging search tasks, we adopt multi-agent reinforcement learning (MARL) to study the problem of multi-AUV cooperative area search from the perspective of improving autonomous decision-making capabilities and collaboration between AUVs. First, we modeled the search task as a decentralized partial observation Markov decision process (Dec-POMDP) and established a search information map. Each AUV updates the information map based on sonar detection information and information fusion between AUVs, and makes real-time decisions based on this to better address the problem of insufficient observation information caused by the weak perception ability of AUVs in underwater environments. Secondly, we established a multi-AUV cooperative area search system (MACASS), which employs a search strategy based on multi-agent reinforcement learning. The system combines various AUVs into a unified entity using a distributed control approach. During the execution of search tasks, each AUV can make action decisions based on sonar detection information and information exchange among AUVs in the system, utilizing the MARL-based search strategy. As a result, AUVs possess enhanced autonomy in decision-making, enabling them to better handle challenges such as limited detection capabilities and insufficient observational information.

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Immobilization of a novel d-allulose 3-epimerase from Bacillus cihuensis within metal-organic frameworks - Ziyi Li; Tao Liu; Wenwen Pei; Yan Zeng; Yan Men; Xuegang Luo; Yueming Zhu; Yuanxia Sun (Food Bioscience, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Flexural vibration suppression behavior of sleeved phononic crystal pipes in thermal environment - Qian Geng; Guangyi Zhao; Xiongwei Yang; Zhushan Shao; Yueming Li (Engineering Structures, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

An Obstacle Avoidance Strategy for AUV Based on State-Tracking Collision Detection and Improved Artificial Potential Field - Yueming Li; Yuhao Ma; Jian Cao; Changyi Yin; Xiangyi Ma (Journal of Marine Science and Engineering, 2024)
This paper proposes a fusion algorithm based on state-tracking collision detection and the simulated annealing potential field (SCD-SAPF) to address the challenges of obstacle avoidance for autonomous underwater vehicles (AUVs) in dynamic environments. Navigating AUVs in complex underwater environments requires robust autonomous obstacle avoidance capabilities. The SCD-SAPF algorithm aims to accurately assess collision risks and efficiently plan avoidance trajectories. The algorithm introduces an SCD model for proactive collision risk assessment, predicting collision risks between AUVs and dynamic obstacles. Additionally, it proposes a simulated annealing (SA) algorithm to optimize trajectory planning in a simulated annealing potential field (SAPF), integrating the SCD model with the SAPF algorithm to guide AUVs in obstacle avoidance by generating optimal heading and velocity outputs. Extensive simulation experiments demonstrate the effectiveness and robustness of the algorithm in various dynamic scenarios, enabling the early avoidance of dynamic obstacles and outperforming traditional methods. This research provides an accurate collision risk assessment and efficient obstacle avoidance trajectory planning, offering an innovative approach to the field of underwater robotics and supporting the enhancement of AUV autonomy and reliability in practical applications.

Nitrogen-doped biochar/MnO2 as an efficient PMS activator for synergistic BPA degradation via non-free radical pathways in the water - Hang Chen; Xiao Li; Weizhuo Li; Jing Feng; Ying Zhao; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2024)

Identification of groundwater pollution sources and health risk assessment in the Fengshui mining area of Central Shandong, China - Hongyu Li; Jiaxin Wu; Yueming Qi; Chengzhi Su; Dan Jiang; Pei Zhou (Environmental Science and Pollution Research, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Wide pH photocatalytic nitrate reduction at adaptive microenvironment-dominated liquid–liquid-solid trilayer reaction interfaces - Xiao Li; Jin Chang; Hexin Zhang; Jing Feng; Jun Ma; Chengying Bai; Yueming Ren (Chemical Engineering Journal, 2024)

Enhanced photocarrier separation in Br substitution-induced [W(VI)O6−x] units for highly efficient photocatalytic nitrate reduction under alkaline conditions - Xiao Li; Jin Chang; Hexin Zhang; Jing Feng; Jun Ma; Chengying Bai; Yueming Ren (Journal of Hazardous Materials, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Identification and stability evaluation of polyphenol oxidase substrates of pineapple fruit - Hai Liu; Jiangming Li; Yueming Jiang; Fengjun Li (Food Chemistry, 2024)

Liraglutide attenuates palmitate-induced apoptosis via PKA/β-catenin/Bcl-2/Bax pathway in MC3T3-E1 cells - Lanlan Cheng; Yijing Xu; Yueming Long; Fangmei Yu; Li Gui; Qiu Zhang; Yunxia Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Trajectory-Following Control of an Unmanned Aerial–Aquatic Vehicle under Complex Coupling Interferences - Jian Cao; Jiayuan Mao; Yueming Li; Le Wang; Biao Cao (Journal of Marine Science and Engineering, 2023)
This article explores trajectory-following control for an unmanned aerial–aquatic vehicle (UAAV) navigating complex ocean disturbances and the interplay of air–seawater coupling factors. First, leveraging the backstepping technology, an adaptive algorithm is proposed to tackle the attitude and position following. Additionally, a nonlinear observer is crafted to estimate complex ocean disturbances. The UAAV model, characterized by six degrees of freedom (DOF) and nonlinear properties, experiences significant pose changes when emerging from water, underscoring the critical importance of precise pose control. Finally, stability analysis and numerical simulations are demonstrated to verify the feasibility and validity of the proposed control strategies.

Transmedia Performance Research and Motion Control of Unmanned Aerial–Aquatic Vehicles - Xiangren Sun; Jian Cao; Yueming Li; Haipeng Li; Weikai Wang (Journal of Marine Science and Engineering, 2023)
This paper presents an improved motion controller based on the backstepping method to address nonlinear control challenges in unmanned aerial–aquatic vehicles (UAAVs), enabling them to navigate between two different media. The nonlinear control approach is applied to UAAV motion control, incorporating filters to improve stability. The study designs motion controllers for three UAAV phases: underwater, in the air, and transitioning between media. Fluid simulations of the emergence process of the UAAV for future field experiments were conducted. By fine-tuning the simulations, a comprehensive understanding of the vehicle’s performance is obtained, offering crucial insights for the development of subsequent control systems. Simulation results confirm the controller’s ability to achieve target trajectory tracking with control system responses that meet practical requirements. The controller’s performance in attitude control and trajectory tracking is verified in underwater gliding, transmedia transitions, and airborne phases, demonstrating its effectiveness.

Fe mediated alleviation effect of cadmium toxicity in mangrove Avicennia marina (Forssk.) Vierh - Jian Li; Yueming Wu; Xiaotong Guo; Shan Jiang; Zhanrui Leng; Jiaojiao Xia; Chongyu Zhuo; Hui Jia; Daolin Du (Frontiers in Marine Science, 2023)
Iron (Fe) supply is one of the key factors in alleviating cadmium (Cd) stress in different plants, including mangroves. However, the effects and mechanisms of Fe in mediating the mangrove response to Cd stress still need to elaborate on the level of plant physiology and metabolism. Herein a 40-day hydroponic study was conducted to evaluate the mediating effect of Fe on Cd tolerance of Avicennia marina (Forssk.) Vierh. Results showed that the Fe supply directly improved the activity of ferric chelate reductase (FCR), increased Fe concentration in tissues, enhanced its competitiveness with Cd, and improved Fe bioavailability, thereby reducing the uptake of Cd by plants. Simultaneously, moderate Fe enhanced the photosynthesis and increased concentrations of total phenolics and tannins in both roots and leaves that play a critical role in chelating and immobilizing Cd, thus restricting the Cd translocation from roots to aboveground tissues. Additionally, the application of Fe significantly upregulated the activity of antioxidant enzymes, including POD and PPO and hence scavenging the reactive oxygen species caused by Cd stress. In conclusion, moderate Fe application improved the growth of A. marina and enhanced its tolerance to Cd at physiological and metabolic levels. Therefore, improving Fe bioavailability will reduce the mangrove degradation caused by Cd contamination, and also this may be a potential way to restore contaminated mangrove ecosystems. Protecting and restoring mangroves is not only essential for preserving biodiversity and supporting coastal ecosystems but also crucial for maintaining their role as crucial carbon sinks (i.e., mangrove blue carbon) combating global warming and climate change.

Hexaconazole and binary mixtures of it plus fludioxonil efficiently control tomato leaf mold caused by Cladosporium fulvum - Shuai Hu; Xiuhuan Li; Lele Chen; Yueming Wu; Lingtao Meng; Kai Wang; Beixing Li; Feng Liu (Crop Protection, 2023)

Insight into the crack characteristics and mechanisms of retrogressive slope failures: A large-scale model test - Yueming Yin; Qinglu Deng; Weibo Li; Kai He; Zhenghong Wang; Haijun Li; Pengju An; Kun Fang (Engineering Geology, 2023)

Coupling strength between omnivory loops and their one-species-delete subloops drives real food web stability - Jianfeng Feng; Shengpeng Li; Xiaoxiao Li; Yueming Jiang; Ruyue Wang; Xianhao Meng; Wei Yang; Tao Sun; Peter C. de Ruiter; Yongtang Shi; Nils Chr. Stenseth (Theoretical Ecology, 2023)

Ubiquitin ligase enzymes and de-ubiquitinating enzymes regulate innate immunity in the TLR, NLR, RLR, and cGAS-STING pathways - Wang Jiang; Mengling Li; Siyuan Peng; Tian Hu; Yan Long; Jiayi Zhang; Dan Peng; Yueming Shen (Immunologic Research, 2023)

Increased aerosol scattering contributes to the recent monsoon rainfall decrease over the Gangetic Plain - Tong Ying; Jing Li; Zhongjing Jiang; Guanyu Liu; Zhenyu Zhang; Lu Zhang; Yueming Dong; Chuanfeng Zhao (Science Bulletin, 2023)

Research on the hydrodynamic performance of AUVs in small size open channel area - Jian Cao; Yaoqi Feng; Yueming Li; Hongwei Li; Chao Han; Yushan Sun; Zhaohang Liu (Ocean Engineering, 2023)

H2O2-activated transcription factor MdERF4 negatively regulates ethylene biosynthetic during fruit ripening by suppressing MdACS1 transcription - Nannan Zang; Xiaojing Li; Liyong Qi; Zhuoran Zhang; Yueming Yang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2023)

Underwater object tracker: UOSTrack for marine organism grasping of underwater vehicles - Yunfeng Li; Bo Wang; Ye Li; Zhuoyan Liu; Wei Huo; Yueming Li; Jian Cao (Ocean Engineering, 2023)

Relationship between summer time near-surface ozone concentration and planetary boundary layer height in Beijing - Chongzhao Zhang; Zhongjing Jiang; Meijing Liu; Yueming Dong; Jing Li (Atmospheric Research, 2023)

Retrieval of aerosol single scattering albedo using joint satellite and surface visibility measurements - Yueming Dong; Jing Li; Xing Yan; Chong Li; Zhongjing Jiang; Changrui Xiong; Liang Chang; Lu Zhang; Tong Ying; Zhenyu Zhang (Remote Sensing of Environment, 2023)

Microbiota of a seepage face at the mouth of a subterranean estuary: diversity, distribution and substrate dependence - Yueming Wu; Yongjun Wei; Juan Severino Pino Ibánhez; Danqing Sun; Kaiqi Lu; Qianqian Wang; Jian Li; Shan Jiang (Acta Oceanologica Sinica, 2023)

Characterization of nongxiang- and soy sauce-type distilled grains and their application in enhancing polyunsaturated fatty acid and triacylglyceride production from Chlorella sp. 038F - Na Yang; Jingjing Shangguan; Litao Zhang; Yueming Li; Jianchun Xu; Xiuluan Xia; Jianguo Liu (Journal of Environmental Chemical Engineering, 2023)

The roles of exogenous ATP in postharvest fruit and vegetable: A systematic meta-analysis - Youxia Shan; Shuting Zhang; Ying Li; Jun Zhang; Mohamed A. Farag; Jun-Xian He; Jianbo Xiao; Hongxia Qu; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2023)

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

High-ratio {100} plane-exposed ZnO nanosheets with dual-active centers for simultaneous photocatalytic Cr(VI) reduction and Cr(III) adsorption from water - Xiao Li; Jiajia Liu; Jing Feng; Tong Wei; Zhongxiang Zhou; Jun Ma; Yueming Ren; Yanqing Shen (Journal of Hazardous Materials, 2023)

Flavor substances of low-valued red swamp crayfish (Procambarus clarkii) hydrolysates derived from double enzymatic systems - Chujun Li; Zongcai Tu; Wenyu Liu; Chunlin Wu; Yueming Hu; Hui Wang (Food Research International, 2023)

MaMYB13 is involved in response to chilling stress via activating expression of VLCFAs and phenylpropanoids biosynthesis-related genes in postharvest banana fruit - Zhiwei Li; Yijie Zhou; Hanzhi Liang; Qing Li; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Food Chemistry, 2023)

A NAC transcriptional factor BrNAC029 is involved in cytokinin-delayed leaf senescence in postharvest Chinese flowering cabbage - Fengjun Li; Youxia Shan; Haobin Wang; Guoxiang Jiang; Xiaochun Ding; Hanzhi Liang; Chunlan Wang; Xiangjin Kong; Lihong Xie; Yueming Jiang (Food Chemistry, 2023)

Involvement of miRNAs-mediated senescence and salicylic acid defense in postharvest litchi downy blight - Chunxiao Yin; Lihong Xie; Yanfei Wu; Hongxia Qu; Bao Yang; Liang Gong; Yueming Jiang; Taotao Li (Food Chemistry, 2023)

Heat transfer behavior of an immersed tube with sCO2 working fluid in a hot fluidized bed at high pressure - Yu Huang; Xu Bao; Yuanqiang Duan; Lin Li; Dongdong Fang; Yueming Wang; Lunbo Duan (Fuel, 2023)

Study on structure-activity relationship (SAR) of simplified mirogabalin derivatives as voltage-gated calcium channel α2δ ligands for the treatment of chronic neuropathic pain - Yuanwen Zhang; Yueming Zheng; Qingqing Wu; Fuyun Tian; Chuanjun Ma; Haiyan Xu; Li Zhan; Zhaobing Gao; Guilong Zhao; Huihui Ti (Medicinal Chemistry Research, 2023)

Construction of a Diagnostic Model for Distinguishing Benign or Malignant Bone Cancer by Mining miRNA Expression Data - Yueming Zhang; Jianwei Hu; Tao Li; Shizhu Hao; Xiaotang Wu (Biochemical Genetics, 2023)

Correction to: Effects of Sub-chronic Lead Exposure on Essential Element Levels in Mice - Shaojun Li; Chun Yang; Xiang Yi; Ruokun Wei; Michael Aschner; Yueming Jiang; Shiyan Ou; Chaocong Yao (Biological Trace Element Research, 2023)

Effects of Sub-chronic Lead Exposure on Essential Element Levels in Mice - Shaojun Li; Chun Yang; Xiang Yi; Ruokun Wei; Michael Aschner; Yueming Jiang; Shiyan Ou; Chaocong Yao (Biological Trace Element Research, 2023)

MiR-139-5p/ENAH Affects Progression of Hepatocellular Carcinoma Cells - Yueming Zhang; Meng Li; Yinghuan Qiu; Yuhua Wu; Shan Chen; Bin Ni; Ding Tang; Zhouzi Deng; Zhiqiang Hu (Biochemical Genetics, 2022)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Simulation and risk assessment of typical antibiotics in the multi-media environment of the Yangtze River Estuary under tidal effect - Chaomeng Dai; Yueming Han; Yan Li; Yanping Duan; Shuguang Liu; Yalei Zhang; Yaojen Tu (Environmental Science and Pollution Research, 2022)

Consequences of Coastal Wetlands Reclamation and the Need for Integrating Impact Assessment of Invasive Alien Plants Species and Coastal Armoring in Life Cycle Assessment (LCA) - Taitiya Kenneth Yuguda; Zhanrui Leng; Yueming Wu; Hui Jia; Sai Zhang; Zhicong Dai; Jian Li; Daolin Du (International Journal of Environmental Research, 2022)

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Seasonal Variation of Food Web Structure and Stability of a Typical Artificial Reef Ecosystem in Bohai Sea, China - Shengpeng Li; Ruyue Wang; Yueming Jiang; Yanyu Li; Lin Zhu; Jianfeng Feng (Frontiers in Marine Science, 2022)
The last 30 years have witnessed the degradation and loss of function in the ecosystem of the Bohai Sea, China. Great efforts, such as artificial reefs, have been used to restore the ecosystem of the Bohai Sea in recent years. In this study, we examined the seasonal variation of food webs in artificial reefs of Juehua Island by the Ecopath model. Results showed that the number of species, range of trophic level, energy cycle proportion, energy complexity, nutrition transfer efficiency, and ecosystem maturity have increased from summer to autumn. However, the food web stability of artificial reefs has no obvious change from summer to autumn. Loop analysis revealed that the heaviest feedback loops are the interactions among benthos, zooplankton, and phytoplankton, and the predator-prey negative interaction strength between zooplankton and phytoplankton dominated the stability of the artificial reef, whether in summer or autumn. This study suggests that stability is a more robust indicator for ecosystem assessment and could provide useful information in future restoration plans of the marine ecosystem.

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Representativeness and Redundancy-Based Band Selection for Hyperspectral Image Classification` - Yufei Liu; Xiaorun Li; Yueming Feng; Liaoying Zhao; Wenqiang Zhang (International Journal of Remote Sensing, 2021)

A spatial-spectral clustering-based algorithm for endmember extraction and hyperspectral unmixing - Xiaoyu Cheng; Zhouyin Cai; Jia Li; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

ATP-binding cassette g1 regulates osteogenesis via Wnt/β-catenin and AMPK signaling pathways - Lei Zhou; Shiwei Sun; Tieqi Zhang; Yueming Yu; Liang Xu; Haoran Li; Minghai Wang; Yang Hong (Molecular Biology Reports, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Aquaculture area extraction and vulnerability assessment in Sanduao based on richer convolutional features network model - Yueming Liu; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Fengshuo Yang (Journal of Oceanology and Limnology, 2019)

Object-based classification of cloudy coastal areas using medium-resolution optical and SAR images for vulnerability assessment of marine disaster - Fengshuo Yang; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Yueming Liu (Journal of Oceanology and Limnology, 2019)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Proteomic and transcriptomic analysis to unravel the influence of high temperature on banana fruit during postharvest storage - Taotao Li; Qixian Wu; Xuewu Duan; Ze Yun; Yueming Jiang (Functional & Integrative Genomics, 2019)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

Long-term exposure to low level of fluoride induces apoptosis via p53 pathway in lymphocytes of aluminum smelter workers - Pingjing Wen; Xiaomin Wei; Guiqiang Liang; Yanfei Wang; Yiping Yang; Lilin Qin; Weiyi Pang; Guangqiu Qin; Hai Li; Yueming Jiang; Qijun Wu (Environmental Science and Pollution Research, 2019)

Spatiotemporal development of mine water inrush and its mechanism—a case study in Ganhe coal mine, Shanxi, China - Yueming Qi; Minzu Li; Kuangjia Li; Tian-Chyi Jim Yeh (Arabian Journal of Geosciences, 2017)

The Adsorption Behavior of Pb2+ and Cd2+ in the Treated Black Soils with Different Freeze-Thaw Frequencies - Xu Wang; Yueming Li; Na Mao; Yanqiu Zhou; Ping Guo (Water, Air, & Soil Pollution, 2017)

Molecular characterization and evolutionary origins of farinin genes in Brachypodium distachyon L. - Saminathan Subburaj; Nana Luo; Xiaobing Lu; Xiaohui Li; Hui Cao; Yingkao Hu; Jiarui Li; Yueming Yan (Journal of Applied Genetics, 2016)

Treatment of cauda equina syndrome caused by lumbar disc herniation with percutaneous endoscopic lumbar discectomy - Xiaolong Li; Qingyu Dou; Shuai Hu; Jiaxiang Liu; Qingquan Kong; Jiancheng Zeng; Yueming Song (Acta Neurologica Belgica, 2016)

Zircon ages and geochemical data of the Biluutiin ovoo ophiolite: implication for the tectonic evolution of South Mongolia - Mingshuai Zhu; Laicheng Miao; Munkhtsengel Baatar; Fochin Zhang; Chimedtseren Anaad; Shunhu Yang; Yueming Li (International Geology Review, 2014)

Molecular characterisation and evolution of HMW glutenin subunit genes in Brachypodium distachyon L. - Saminathan Subburaj; Guanxing Chen; Caixia Han; Dongwen Lv; Xiaohui Li; Friedrich J. Zeller; Sai L. K. Hsam; Yueming Yan (Journal of Applied Genetics, 2014)

Natural Occurrence, Analysis, and Prevention of Mycotoxins in Fruits and their Processed Products - Jinyi Yang; Jing Li; Yueming Jiang; Xuewu Duan; Hongxia Qu; Bao Yang; Feng Chen; Dharini Sivakumar (Critical Reviews in Food Science and Nutrition, 2014)

Selection of surfactant in remediation of DDT-contaminated soil by comparison of surfactant effectiveness - Ping Guo; Weiwei Chen; Yueming Li; Tao Chen; Linhui Li; Guanzhu Wang (Environmental Science and Pollution Research, 2014)

Experimental Research on the In Vitro Antitumor Effects of Crataegus sanguinea - Jianling Sun; Guolan Gao; YuLian Gao; liJuan Xiong; Xiaoying Li; Jihong Guo; Yueming Zhang (Cell Biochemistry and Biophysics, 2013)

Integrating fuzzy logic with piecewise linear regression for detecting vegetation greenness change in the Yukon River Basin, Alaska - Yueju Xue; Shuguang Liu; Li Zhang; Yueming Hu (International Journal of Remote Sensing, 2013)

Removal of heavy metal ions from wastewater by a novel HEA/AMPS copolymer hydrogel: preparation, characterization, and mechanism - Zhengkui Li; Yueming Wang; Ningmei Wu; Qichun Chen; Kai Wu (Environmental Science and Pollution Research, 2013)

Molecular characterization and dynamic expression patterns of two types of γ-gliadin genes from Aegilops and Triticum species - Shunli Wang; Xixi Shen; Pei Ge; Jie Li; Saminathan Subburaj; Xiaohui Li; F. J. Zeller; S. L. K. Hsam; Yueming Yan (Theoretical and Applied Genetics, 2012)

Overexpression of d-psicose 3-epimerase from Ruminococcus sp. in Escherichia coli and its potential application in d-psicose production - Yueming Zhu; Yan Men; Wei Bai; Xiaobo Li; Lili Zhang; Yuanxia Sun; Yanhe Ma (Biotechnology Letters, 2012)

Phylogenetic relationship of a new class of LMW-GS genes in the M genome of Aegilops comosa - Ke Wang; Liyan Gao; Shunli Wang; Yanzhen Zhang; Xiaohui Li; Miaoyi Zhang; Zhenze Xie; Yueming Yan; Matthew Belgard; Wujun Ma (Theoretical and Applied Genetics, 2011)

Identification and characterization of a novel l-arabinose isomerase from Anoxybacillus flavithermus useful in d-tagatose production - Yanjun Li; Yueming Zhu; Anjun Liu; Yuanxia Sun (Extremophiles, 2011)

Molecular characterization of the celiac disease epitope domains in α-gliadin genes in Aegilops tauschii and hexaploid wheats (Triticum aestivum L.) - Zhenze Xie; Congyan Wang; Ke Wang; Shunli Wang; Xiaohui Li; Zhao Zhang; Wujun Ma; Yueming Yan (Theoretical and Applied Genetics, 2010)

Overexpression and characterization of a thermostable trehalose synthase from Meiothermus ruber - Yueming Zhu; Dongsheng Wei; Jun Zhang; Yufan Wang; Hengyi Xu; Laijun Xing; Mingchun Li (Extremophiles, 2010)

Preserved amplitude migration based on the one way wave equation in the angle domain - Yueming Ye; Zhenchun Li; Xufeng Zhu; Zhaoqi Tong (Applied Geophysics, 2009)

Post-stack reverse-time migration using a finite difference method based on triangular grids - Shujuan Guo; Zhenchun Li; Xiaodong Sun; Yueming Ye; Houhua Teng; Fang Li (Applied Geophysics, 2008)

Cloning and characterization of a novel low molecular weight glutenin subunit gene at the Glu-A3 locus from wild emmer wheat (Triticum turgidum L. var. dicoccoides) - Xiaohui Li; Aili Wang; Yinghua Xiao; Yueming Yan; Zhonghu He; Rudi Appels; Wujun Ma; S. L. K. Hsam; F. J. Zeller (Euphytica, 2008)

Beamlet prestack depth migration and illumination: A test based on the Marmousi model - Yueming Ye; Zhenchun Li; Wengong Han; Qingmin Liu (Applied Geophysics, 2006)

Genetic diversity of European spelt wheat (Triticum aestivum ssp. spelta L. em. Thell.) revealed by glutenin subunit variations at the Glu-1 and Glu-3 loci - Xueli An; Qiaoyun Li; Yueming Yan; Yinghua Xiao; S.L.K. Hsam; F.J. Zeller (Euphytica, 2005)

Experimental study on full-scale steel beam-to-column moment connections - Jiaru Qian; Haiqun Yu; Feng Yan; Hai Dong; Jianhua Li; Yueming Liu (Earthquake Engineering and Engineering Vibration, 2005)

Durchlässigkeitseigenschaften und Drainagemaßnahmen von RCC-Staumauern - Yueming Zhu; Stephan Semprich; Erich Bauer; Jing Li (WASSERWIRTSCHAFT, 2005)